Global genomic methylation related to the degree of parasitism in cattle - de Soutello, Ricardo Velludo Gomes [UNESP]; Rodrigues, Maria Gabriela Fontanetti [UNESP]; Gonçalves, Juliana Alencar [UNESP]; Bello, Hornblenda Joaquina Silva [UNESP]; Pavan, Bruno Ettore [UNESP]; Ramos, Ester Silveira (Springer Nature, 2022)
The objective of the present study was to characterize a herd of 72 ½ Angus × ½ Nellore heifers, identify the resistant, resilient and susceptible animals to parasites, relate the overall DNA methylation of these animals with the degree of parasitism, evaluated by the egg count per gram of feces (EPG), Haematobia irritans count (horn fly) and Rhipicephalus microplus count (bovine tick). The experiment was carried out in a completely randomized design, containing 72 treatments, with each animal considered a treatment, and 11 repetitions, with each collection within a year considered a repetition. The data obtained from the counts of the evaluated parasites were subjected to statistical analysis using the SISVAR program, to classify heifers according to the degree of parasitism in low (resistant), intermediary (resilient) and high (susceptible) parasite load for infection by nematodes, infestation by ticks and flies. Addition the animals in these three groups, by hierarchical grouping using the GENES program, heifers were classified as to the degree of parasitism by the three parasites along with the DNA methylation content of the animals in each group. A negative relationship was observed between resistance and methylated DNA content in both classifications, with the resistant, resilient, and susceptible animals showing the highest, intermediate, and lowest methylated DNA quantifications, respectively. Thus, the methodologies used herein enabled the classification of 72 heifers according to the degree of collective infection by gastrointestinal nematodes and infestation by ticks and horn flies, thereby establishing a link between the degree of parasitic resistance in cattle and the global methylated DNA quantification.